(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
This study was conducted to find out the effect of feeding Leucaena leucocephala leaf meal on growth performance and digestibility of nutrients in growing rabbit and to know the cost of rabbit production. For this purpose, a total of twelve unsexed New Zealand White rabbits at 42 days of age were distributed randomly in three treatment groups, i.e. control (T0), adding 10% Leucaena leucocephala leaf meal (T1) in concentrate diet and adding 15% Leucaena leucocephala leaf meal (T2) in concentrate diet. All diets were iso-energic and iso-nitrogenous. Various aspects of the study, measurements taken in a 56 days experimental period were final body weight gain, feed intake, feed conversion ratio and feeding cost of rabbit production. Results show that the final body weight of rabbits was 1200±30, 1325±85 and 1114±136g, for the treatments of T0, T1 and T2, respectively. The body weights of rabbits were significantly higher in T1 over T2 and T0 groups. The average daily feed intake and feed conversion ratio were 109, 75.55, 83.57g and 9.55, 5.48 and 8.51 for the respective diets/treatments. The growth rate of T0, T1 and T2 treatment groups were 1.05, 1.44 and 0.99, respectively. There was significant effect of different treatment groups on growth rate, feed intake and feed conversion ratio (FCR). The digestibility of dry matter (DM) was the highest in diet T0 followed by diet T2 and T1, respectively. The digestibility of CP was slightly higher for treatment T2 containing 15% Leucaena dry leaf than that of treatment T0 and T1. The digestibility of crude fiber (CF) and ether extract was significantly (P<0.01) difference among the treatment groups. The highest NFE digestibility was recorded for diet T0 and lowest for diet T1. The costs of these three concentrate mixture were 24.43, 21.48 and 20.21Tk/kg for diet T0, T1 and T2, respectively. The reduction of feed cost of producing 1 kg live weight was by 53% in T1 and by 31% in T2 group from T0 group. It may be concluded that Leucaena leucocephala leaf meal at 10% inclusion level may be used as an alternative source of protien in the diet of rabbit as there was no adverse effect (toxicity) on feed consumption and feed conversion ratio. It may be recommended that adding 10% level of Leucaena leucocephala leaf meal of the diet for economic rabbit meat production. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (2), 261-267